PID TUNING OF DC MOTOR USING SWARM ITELLIGENCE ALGORITHM - Hasdi Aimon, Arhimny (Universiti Teknologi PETRONAS, 2012)
In this project, Particle Swarm Optimization (PSO) as one of Swarm Intelligence Algorithm based has proposed to be integrated with PID (Proportional, Integral, Derivative) Controller in order to achieve optimal tuning method. PSO-PID Controller is employed to improve the control performance of DC Motor. PSO-PID Controller has successfully eliminated the overshoot at the same time had faster response time. Inertia Weight PSO (IWPSO) and Constriction Factor PSO (CFPSO) are also employed in this project. Both of them verify to be able to improve the convergence of swarm by showing smaller value of MSE. CFPSO-PID Controller has regarded as the best tuning method since it results the best control performance and smaller value of MSE. The simulation is performed both in C++ and MATLAB. PSO-PID Controller algorithm is performed in C++. The results will be the optimal value of controller parameters. In order to evaluate the control performance, the three control parameters will be used to tune DC Motor simulated in MATLAB. PSO-PID Controller Graphical User Interface (GUI) has developed that integrates both C++ and MATLAB program for more practical use.